2002
DOI: 10.4141/a01-017
|View full text |Cite
|
Sign up to set email alerts
|

Methane production from dairy and beef heifers fed forages differing in nutrient density using the sulphur hexafluoride (SF6) tracer gas technique

Abstract: . 2002. Methane production from dairy and beef heifers fed forages differing in nutrient density using the sulphur hexafluoride (SF 6 ) tracer gas technique. Can. J. Anim. Sci. 82: [201][202][203][204][205][206]. The effects of cattle breed type [dairy (Holstein) versus beef (Charolais × Simmental)] and forage quality (high, medium and low) on methane production were measured under ad-libitum and restricted feeding conditions. The in vitro organic matter digestibility (IVOMD) of the forage diets was high = 61.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
59
3
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(75 citation statements)
references
References 12 publications
8
59
3
2
Order By: Relevance
“…No further in vivo data are available to support our findings on grass silage-fed dairy cows. However, the present results are in line with a study of Boadi and Wittenberg (2002) in which medium-quality grass hay (50.7% in vitro OM digestibility) generated 10% more CH 4 per unit of DOMI than high-quality grass hay (61.5% in vitro OM digestibility) offered restrictedly to dairy and beef heifers, and in line with a study of Pinares-Patiño et al (2003) in which Charolais cows grazing timothy at heading stage (74.8% OM digestibility based on faecal N index method) produced 12% more CH 4 per unit of DOMI than when grazing timothy at early-vegetative stage (77.6% OM digestibility). In contrast, when dairy cows were offered grass herbage under zero-grazing conditions (Warner et al, 2015), CH 4 per unit of DOMI was not affected by either grass maturity or N fertilisation rate, whereas CH 4 declined by 9% per unit of DNDFI with high-compared with low-fertilised grass (90 v. 20 kg of N/ha, respectively).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…No further in vivo data are available to support our findings on grass silage-fed dairy cows. However, the present results are in line with a study of Boadi and Wittenberg (2002) in which medium-quality grass hay (50.7% in vitro OM digestibility) generated 10% more CH 4 per unit of DOMI than high-quality grass hay (61.5% in vitro OM digestibility) offered restrictedly to dairy and beef heifers, and in line with a study of Pinares-Patiño et al (2003) in which Charolais cows grazing timothy at heading stage (74.8% OM digestibility based on faecal N index method) produced 12% more CH 4 per unit of DOMI than when grazing timothy at early-vegetative stage (77.6% OM digestibility). In contrast, when dairy cows were offered grass herbage under zero-grazing conditions (Warner et al, 2015), CH 4 per unit of DOMI was not affected by either grass maturity or N fertilisation rate, whereas CH 4 declined by 9% per unit of DNDFI with high-compared with low-fertilised grass (90 v. 20 kg of N/ha, respectively).…”
Section: Discussionsupporting
confidence: 93%
“…A recent study with lactating cows indicated a substantial reduction (−15%) in CH 4 yield per unit of digestible organic matter intake (DOMI) for early-cut compared with late-cut (cut 3 weeks later) ryegrass-clover silage (Brask et al, 2013). Similar findings were reported for beef and dairy cattle fed various grass hay qualities (Boadi and Wittenberg, 2002).…”
Section: Introductionsupporting
confidence: 54%
“…Overall, straws produced relatively more methane compared with forages. Boadi & Wittenberg (2002) also found that methane production (L/kg digestible OM intake) was 25% higher for low quality forages than medium or high nutritional quality diets. Again, increasing the levels of green fodder such as berseem, oat and sorghum in straw-and stover-based diets may lower methane production.…”
mentioning
confidence: 86%
“…The IPCC Tier-1 emission factors (kg CH 4 head -1 yr -1 ) used were: 56 for dairy heifers; 118 for dairy cows; 75 for bulls; 72 for beef cows; 56 for beef heifers; 47 for calves; 47 for steers; and 47 for heifers for slaughter (IPCC 1997;Olsen et al 2003). Emission factors generated from CRS were based on the following studies: (1) Boadi and Wittenberg (2002) in which yearling dairy heifers with an initial weight of 310 kg produced 258 L CH 4 d -1 or 6.7% GEI; (2) Kinsman et al (1995) in which lactating dairy cows with an initial weight of 602 kg produced 552 L CH 4 d -1 or 8.9% GEI; (3) Boadi and Wittenberg (2002) in which beef heifers with an initial weight of 310 kg (confined, restricted intake of grass-legume hay) produced 195.8 L CH 4 d -1 or 6.9% GEI ; (4) Boadi and Wittenberg (2002) and in which beef yearling heifers with an initial weight of 310 kg (confined, ad-libitum feeding) produced 258.7 L CH 4 d -1 and beef yearling steers with an initial weight of 262 kg (confined ad-libitum feeding) produced 193.3 L CH 4 d -1 , respectively, with an average methane loss of 6.0% GEI; (6) McCaughey et al (1999) in which first calf cows with an initial body weight of 511.2 kg, grazing grass pastures produced 411.0 L CH 4 d -1 or 9.5% GEI; (7) Ominski et al (2006) in which 343 kg beef yearling steers grazing grass-based pastures produced 198 L CH 4 d -1 or 8.7% GEI, and (8) Boadi et al (2004b) in which feedlot steers with an initial body weight of 252 kg fed a diet con- For some classes of cattle (i.e., bulls), CRS have not been conducted, and therefore the most appropriate Y m values reported in the literature were used. As described above, for most categories, the time that cattle are in a given production is less than a year.…”
Section: Comparison Of Methodologiesmentioning
confidence: 99%
“…The IPCC Tier-1 emission factors (kg CH 4 head -1 yr -1 ) used were: 56 for dairy heifers; 118 for dairy cows; 75 for bulls; 72 for beef cows; 56 for beef heifers; 47 for calves; 47 for steers; and 47 for heifers for slaughter (IPCC 1997;Olsen et al 2003). Emission factors generated from CRS were based on the following studies: (1) Boadi and Wittenberg (2002) For some classes of cattle (i.e., bulls), CRS have not been conducted, and therefore the most appropriate Y m values reported in the literature were used. As described above, for most categories, the time that cattle are in a given production is less than a year.…”
mentioning
confidence: 99%